CIRCULATORY ARREST WITH SUCCESSFUL RESUSCITATION AND PREVENTION OF RELAPSE IN A PATIENT WITH THE BRUGADA SYNDROME (CLINICAL OBSERVATION) - V. V. Savilova; A. I. Kondratyev; A. O. Stotsky; V. V. Maltsev; S. V. Akulich; S. N. Tsurikov; N. A. Kondratyeva (Неотложная медицинская помощь, 2016)
We report the clinical case and data on the delayed annualmonitoring of a patient with the Brugada syndrome, complicated with the clinical death